Is hypertonic saline an effective alternative to mannitol in the treatment of TBI in adult and pediatric patients? A systematic review and meta-analysis - Qasem Ahmed Almulihi; Asaad Suliman Shujaa; Rawan Yaqob AlKhotani; Saleh Fahad Maqulah; Narjes Ali Alismail; Hussain Ali Alramadhan; Ali Habeeb Alamer; Fatimah Abdulallah Alsayegh; Mustafa Abdulrazaq Alhamood; Ayub Salman Alabdullah; Hamidah Malak Alquraini; Ridha Hussein A. Bohassan; et al. (Saudi Journal of Emergency Medicine, 2023)
Aim: This meta-analysis and systematic review aims to investigate and compare the efficacy of mannitol and hypertonic saline in treating patients who have suffered from traumatic brain injury (TBI). Methods: We reviewed publications from the Medline database, Web of Science, and Google Scholar from inception to 13 October 2022 with only English-based literature. The risk of bias from included Randomized controlled trial (RCT) s was assessed using the Cochrane Collaboration's Tool. Newcastle-Ottawa Scale was employed to assess the included cohort's quality. The main outcomes of this review were treatment failure, mortality, intracranial pressure (ICP) reduction, and Cerebral Perfusion Pressure (CPP) increment. All the statistical analyses were performed using the Review Manager 5.4.1. A random-effects model was used to pool the studies when heterogeneity was seen, and the results were reported in the odds ratios (OR) and mean differences (MD) and the corresponding 95% confidence intervals. Results: The results of the statistical study found that there was a significantly lower treatment failure rate [OR = 1.80 (1.26, 2.57); p = 0.001; I 2 = 74%], the lower mortality rate [OR = 2.17 (1.26, 3.73); p = 0.005; I 2 = 0%], a greater increase in CPP [MD = -1.28 (-2.50, -0.05); p = 0.04; I 2 = 0%] associated with hypertonic saline treatment as compared to mannitol treatment. However, concerning ICP decrease, there was no significant difference between the two treatment options [MD = 1.86 (-0.64, 4.36); p = 0.14; I 2 = 70%]. Conclusions: Quantitative and qualitative analysis of trials and observational studies comparing the efficacy of hypertonic saline and mannitol demonstrates that hypertonic saline is a preferable treatment option with greater effectiveness and safety than mannitol in managing patients with TBI. [SJEMed 2023; 4(1.000): 051-059]